Modifikasi Alat Ukur Interpersonal Reactivity Index (IRI) pada Subjek dengan Identitas Sunda - Tahrir Tahrir; Asmadi Alsa; Anizar Rahayu (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
This study aims to modify the instrument interpersonal reactivity index (IRI) made by Davis (1980) which consists of 4 dimensions into 2 dimensions. This research uses quantitative approach, the respondents is 318 students of UIN Sunan Gunung Djati Bandung who were of Sundanese ethnicity and lived in Islamic boarding schools with simple random sampling. The result of modification IRI instrument from 28 items to 26 items. Based on the results, it is known that content validity shows that all items are valid, the item differences shows that 24 items have a good difference, and confirmatory analysis shows that 23 items are valid. The result of the multidimensional validity test shows that perspective taking aspect has r value .81 and concern for other aspect has r value .71. While the alpha reliability obtained value .903 and reliability CR .96, and the model for empathy instrument of this modification is fit.